Portal biliary ductopathy caused by cavernous transformation of the portal vein. (31st January 2013) - Chong, Jeffrey Chu-Nan; Boyapati, Ray; Rusli, Ferry
Abstract : A 42-year-old woman presented with a 1-week history of epigastric pain and deranged liver function tests (LFTs) on a background of known portal vein thrombosis (PVT) with cavernous transformation. Imaging with ultrasound, CT and MR cholangiopancreatography demonstrated known PVT, with distortion of the common bile duct and a bulky head/proximal body of the pancreas, thought to be due to mass effect from cavernous transformation related to PVT. At endoscopic retrograde cholangiopancreatography, the common hepatic duct was noted to be smaller in diameter, without any filling defects or discrete strictures. Sphincterotomy and balloon trawl was performed, with subsequent improvement of the woman's LFTs and abdominal pain.